2021
DOI: 10.4000/geocarrefour.18491
|View full text |Cite
|
Sign up to set email alerts
|

Activist Surfing-based Groups in the Tourism Transition: Localism and Universalism in the French Basque Country

Abstract: Surfing-based Groups in the Tourism Transition: Localism and Universalism in the French Basque Country https://journals.openedition.org/geocarrefour/18491?lang=en 2/17qui préside à la mobilisation collective. Cet article démontre également que les revendications politiques des surfeurs suggèrent aux pouvoirs publics d'engager un tournant paradigmatique dans la conduite de l'action publique. Dans le cadre du tourisme sportif, il est attendu des pouvoirs publics une transition qui puisse prendre en compte la cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It transformed any tendency for anthropocentricity and replaced it with eccentricity as reported by Brymer and Oades (2009). Indeed, research focusing on emotions and the relationship between humans and the natural environment has revealed that connecting to nature is crucial not only for developing one's identity but also for forming emotional communities of surfers who may go on to become environmental activists (Falaix et al, 2021). The findings are in accordance with those of ), Brymer et al (2020, , Elmahdy et al (2021), Taylor (2007) and Usher (2023) who reported that surfing, as a nature-based sport, creates opportunities for surfers to appreciate, unite and positively connect with nature and other living creatures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It transformed any tendency for anthropocentricity and replaced it with eccentricity as reported by Brymer and Oades (2009). Indeed, research focusing on emotions and the relationship between humans and the natural environment has revealed that connecting to nature is crucial not only for developing one's identity but also for forming emotional communities of surfers who may go on to become environmental activists (Falaix et al, 2021). The findings are in accordance with those of ), Brymer et al (2020, , Elmahdy et al (2021), Taylor (2007) and Usher (2023) who reported that surfing, as a nature-based sport, creates opportunities for surfers to appreciate, unite and positively connect with nature and other living creatures.…”
Section: Discussionmentioning
confidence: 98%
“…Surfers have been found to hold environmentally friendly views as reported by Larson et al (2018). This is reflected in a variety of non-governmental environmental organizations created by surfer-activists such as "Save our Surf " in Hawaii (Walker, 2011), "The Surfrider Foundation" in Southern California, "Surfers Against Sewage" in the UK (Wheaton, 2007), and "Paddle out for your Planet" in France (Falaix et al, 2021). These organizations strive to protect surf breaks, advance the positive qualities of the surfing culture, and preserve biodiversity (Taylor, 2007).…”
Section: Benefits Of Connection With Naturementioning
confidence: 99%